Efeitos da amostragem não-aleatória e do tamanho da amostra na estimação de dois caracteres do milho - SILVA, PAULO SERGIO LIMA E; BEZERRA, AURIBERGUIS ROCHA; OLIVEIRA, FABIO HENRIQUE TAVARES DE; SILVA, KATHIA MARIA BARBOSA E (Revista Ceres, 2015)
.